If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) = 2x + x + 6 Reorder the terms: 3(2 + x) = 2x + x + 6 (2 * 3 + x * 3) = 2x + x + 6 (6 + 3x) = 2x + x + 6 Reorder the terms: 6 + 3x = 6 + 2x + x Combine like terms: 2x + x = 3x 6 + 3x = 6 + 3x Add '-6' to each side of the equation. 6 + -6 + 3x = 6 + -6 + 3x Combine like terms: 6 + -6 = 0 0 + 3x = 6 + -6 + 3x 3x = 6 + -6 + 3x Combine like terms: 6 + -6 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2a+42=-26 | | X=333-2x | | 3x^2=11x+4 | | 7+(1+5n)+6+24n=13 | | 28=10+(-6x) | | 6x+2y-9(5x-4y)= | | -4(3y-10)+3(2y+7)= | | -15+7x=20 | | 25-(3x+2)=2 | | (8y-3)(2y+1)=0 | | 2x+2=3x-men | | 1/8(5y+65)=1/4(20+2y) | | x+3x+x/2-225 | | -5.9x-5.8=-5.5x-5.4 | | 7/10x=392 | | 6x^2-11x=-5 | | 5y-8-2y+7=0 | | 42=18-3x | | -2/3(3/2a-1)+5/6 | | 6x^2-11x=5 | | 9p+6=14+8p | | -3/4a=-5/8 | | 6(5/7+4/63) | | X(6x-11)=5 | | 4(x+2)+2(x-7)-3(x+1)= | | p=6-2q | | 1=-5(4x+2)+21x | | -1/3q=2/3 | | 8x-10=8x+11 | | -24=11v | | 5a+3-b+1= | | 2/3-1/8 |